GENDER MAINSTREAMING AND THE EFFECTIVENESS OF PEACE AGREEMENTS: EVIDENCE FROM SUB-SAHARAN AFRICA - Chukwumeziri Nnatu, Angus; Lawrence Okorozoh, Ugochukwu (African Journal of Social and Behavioural Sciences, 2026)
This study examines the extent to which gender mainstreaming in peace agreements influences their durability in Sub-Saharan Africa (SSA). The analysis is grounded in Feminist Peace Theory and draws on empirical data derived from the PA-X Peace Agreements Database, United Nations Women reports, National Action Plans (NAPs), and key informant interviews. A dataset comprising peace agreements across SSA (2000–2025) was constructed using systematic document coding and triangulated with institutional indicators, including state capacity, conflict intensity, and third-party involvement. Descriptive, correlational, and multivariate regression analyses reveal that higher levels of gender mainstreaming operationalized through the Gender Mainstreaming Index (GMI) are significantly associated with increased peace agreement durability. State capacity and credible third-party guarantees also exert strong positive effects, while conflict intensity demonstrates a negative relationship with sustainability. The findings provide robust empirical support for the argument that inclusive peace processes enhance legitimacy, implementation quality, and long-term stability. The study contributes to the growing body of literature linking gender inclusion to peace outcomes by offering region-specific quantitative evidence and identifying key mediating and moderating factors. It further provides actionable policy insights for governments, regional organizations, and international actors seeking to operationalize UNSCR 1325 and strengthen sustainable peace-building in SSA.